Pemulihan Ekonomi melalui Pengembangan UMKM di Masa New Normal Covid-19: Pendekatan ANP-BCOR - Ahmad Albar Tanjung; Kartika Sari Lubis; Riandani Rezki Prana; Muliyani Muliyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
MSMEs are crucial to Indonesia's economic recovery following the COVID-19 outbreak. The goal of this research is to develop a strategy for MSMEs in Medan to survive and thrive under the new normal conditions of Covid-19. The government must take steps and make attempts to address the issues at hand. Numerous alternative options will be evaluated, including human resource quality enhancement, stakeholder engagement, and collaboration enhancement, digital marketing optimization, product differentiation, and product quality standardization. The Analytic Network Process and Benefits Opportunities Cost Risk (BOCR) techniques are used in this investigation. The objective is to obtain a priority ranking of options to use as a guide when making decisions. BOCR analysis employs three criteria when determining alternative priorities: Standard (B/C), Pessimistic B/ (C x R), and Realistic (BxO)/(C x R). The results of this study indicate that if the decision maker focuses on Realistic, the first priority is Digital Marketing Optimization with a coefficient of 0.19, the second priority is Human Resources Quality Improvement with a coefficient of 0.10, the third priority is Product Quality Standardization with a coefficient of 0.07, the fourth priority is Increased Commitment and Collaboration Stakeholders with a coefficient of 0.02 and the last priority is Product Differentiation with a coefficient of 0.01. With the shift from traditional to digital marketing, the MSME market's reach is no longer restricted to the immediate vicinity, but also extends to locations outside the island and abroad. Increased sales will boost the revenue of MSME actors, contributing to the country's economic recovery. Additionally, developing MSMEs requires the dedication, cooperation, and participation of the government, academia, researchers, financial institutions, and information technology businesses.